Validating a Qualitatively-Developed Model of Classroom Management Strategies in Iranian context - Seyed Fouad Khatib; Mohammad Sadegh Bagheri; Firooz Sadighi; Ehsan Rassaei (Journal of Modern Research in English Language Studies)
The present research was an attempt to posit a model of classroom management strategies for Iranian EFL learners to provide a better interpretation of qualitative findings. Hence, in line with the components of the previous model, a 33-item questionnaire was considered in the design of the classroom management questionnaire. A 42 item researcher-made questionnaire was piloted with 180 EFL learners and its reliability and the related validates were checked. As a result, EFA findings corroborated a 3- component classroom management questionnaire. Finally, the 33-item questionnaire of classroom management was distributed to 360 EFL learners. Then, the initial structure of the model was tested using CFA to come up with the final model of classroom management strategy. The results substantiated the initial structure of EFA with 3 factors and 33 items. The findings suggest EFL teachers not only pay attention to classroom practices, but also work on building up rapport and encouragement with their students. Also, the results can be presented to student teachers in teacher education programs to make them aware of the nuances of classroom management and the concerns of EFL learners in Iran. Further, these results can be at the disposal of any teacher to effectively plan, manage, develop interpersonal relationships and run their classes.